Determinants of the Quality of Financial Reports of Blud Community Health Centers in Pekanbaru City - Raudhatul Jannah AR; R. Septian Armel; Wira Ramashar; Mentari Dwi Aristi (Universitas KH. Abdul Chalim Mojokerto, 2025)
The Public Health Center (BLUD) must prepare two types of financial reports: one as an accounting entity to be consolidated with the Health Office, and the other as a reporting entity to be audited by an external auditor. Therefore, the Public Health Center (BLUD) prepares two reports: one for consolidation, which is prepared following Government Accounting Standards (SAP), while the other for the reporting entity, which is prepared in accordance with Financial Accounting Standards (SAK). The objective of this study is to examine the relationship between professionalism, organizational culture, utilization of information technology, and the role of the inspectorate on the quality of financial reports at BLUD Puskesmas in Pekanbaru City. Quantitative research, samples using purposive sampling techniques, and data collection methods by distributing questionnaires via Google Form and sending them directly to each BLUD Health Center. The results of this study indicate that professionalism, organizational culture, and the role of the inspectorate are the three main factors in achieving good quality financial reports, while the use of information technology is not able to be a factor that can support the good quality of the BLUD Puskesmas financial reports in Pekanbaru City.